Factors influencing Assisted Reproductive Technology [ART] Outcome: possible implications for a private and public sector fertility clinic - Nel, Nicole Ashley (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScMedSc)--Stellenbosch University, 2016.